Establishing monarch butterfly overwintering sites for future climates: Abies religiosa upper altitudinal limit expansion by assisted migration - Sáenz-Romero, Cuauhtémoc; Osuna-Vallejo, Verónica; Herrejón-Calderón, Patricia; Pérez-Cruz, Legna A.; Joaquín-Juan, M. Guadalupe; Cruzado-Vargas, Ana Laura; O’Neill, Gregory A.; Zacarías-Correa, Ana Gabriela; Manzanilla-Quijada, Gyorgy E.; Lindig-Cisneros, Roberto; Blanco-García, Arnulfo; Endara-Agramont, Ángel R.; et al. (Frontiers in Forests and Global Change, 2024)
Climate change projections suggest a precarious future for the Monarch butterfly (Danaus plexippus) as the suitable climatic habitat of its exclusive overwintering host Abies religiosa (oyamel, Sacred fir, a conifer endemic to Mexico) inside the Monarch Butterfly Biosphere Reserve (MBBR) is expected to disappear by 2090. Since the upper elevation limit of A. religiosa is approximately 3,500 m and the summits of mountains within the MBBR are ca. 3,550 m, we tested the feasibility of establishing A. religiosa at four locations outside its current geographic range in the MBBR, on a geographically close volcano, Nevado de Toluca at 4000 (timberline, an extreme site), 3,800, and 3,600 m (to test species range expansion upward in elevation), and at 3400 m (a reference site, slightly lower than the upper elevation limit of A. religiosa). Using existing shrubs as nurse plants to protect the seedlings from extreme temperatures, at each site we planted five to eight populations, originating between 3,100 and 3,500 m within the MBBR. After three growing seasons in the field (6 years after sowing), we found that: (a) survival and height increment declined steeply with test site elevation; (b) even at the highest sites (3,800 and 4,000 m), survival was acceptable, at 68 and 44%, respectively, although the growth was very poor at 4000 m; (c) populations responded similarly to transfer; (d) transfer effects were best accounted for by annual dryness index; (e) to compensate for the expected 2.3°C increase in mean annual temperature or 0.009 √°Cmm−1 increase of annual dryness index from the reference period (1961–1990) to the decade centered in 2060, it would be necessary to shift populations approximately 500 m to higher elevations; and (f) upward transfers to compensate for the 2.3°C increase in mean annual temperature are expected to result in height increment and survival that are approximately 47 and 21% lower, respectively, than values expected at zero transfer distance. We conclude that the establishment of A. religiosa at 3600 and 3,800 m is feasible and that planted stands could eventually serve as overwintering sites for the Monarch butterfly under projected future climates.